De l’optimalité pour la « ville verte » - Sébastien Passel (Projets de Paysage)
Today, four French people out of five live in cities. The widespread urbanization in recent decades has led to a deterioration of living conditions in most urban areas (Mathieu and Guermond, 2005). The question of a new urbanity arises through the dynamics of open space distribution that contributes to the optimization of the city structure. A spatial analysis study using mathematical morphology will be conducted to detect the potentialities of Nice’s open spaces system.